Application of paraffin and silver coated titania nanoparticles in polyethylene nanocomposite food packaging films - Hosseini Nasab, Nafiseh; Jalili, Mohammad Mehdi; Farrokhpay, Saeed (Journal of applied polymer science, 2018)
ABSTRACT In this work, 3% and 5% TiO2/Ag nanoparticles were dispersed in low‐density polyethylene through melt blending process, and subsequently nanocomposite films were prepared by hot pressing. Paraffin was used for the first time in this work as compatibilizer agent. The effect of TiO2/Ag nanoparticle content, as well as compatibilizer dosage on the antimicrobial, morphological, mechanical, and optical performance of the nanocomposite films was investigated. Improved mechanical properties of the nanocomposite films were found on using paraffin as compatibilizer in comparison with the neat low‐density polyethylene (LDPE) films. The optical study results also showed that the addition of TiO2/Ag to the LDPE films does not drastically change the film appearance other than making them more reddish. The fabricated nanocomposites presented in this study could be a suitable choice for food packaging (subject to further investigation of the food packaging behavior). The results showed that both TiO2/Ag nanoparticle and compatibilizer are needed to prevent the bacteria growth in the film. The best result was obtained by using 5% nanoparticle and 4% paraffin compatibilizer where the bacteria growth rate was significantly reduced by 95%. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2018, 135, 45913.